The Ancient Origin of HIV - V. P. Sergiev (Эпидемиология и вакцинопрофилактика)
Analysis of scientific publications is revealed that HIV transmission been present among humans for centuries or thousand years. This evidence had been proved by molecular and genetic methods. Additionally, to molecular methods the fact been proved by the presence in humans of a perfect genetic defense against HIV. There is a long co-evolution between humans and their pathogens needed to develop genetic defense mechanisms.